HTTP/2.0 — The IETF Is Phoning It In. - KAMP, POUL-HENNING (Communications of the ACM, 2015)
The article discusses HTTP/2.0, an upgrade to the HTTP Internet protocol proposed by the Internet Engineering Task Force's (IETF's) steering group. Among the author's criticisms of HTTP/2.0 is that it is overly complex, does not address privacy concerns, and continues to use files known as cookies. He further observes that HTTP/2.0 is not faster than its predecessor but does require substantially more computing power. In his view the IETF is proposing what he considers to be a mediocre protocol to safeguard its relevance at a time when Internet-search firm Google has developed a rival SPDY protocol.